Bimodal immune activation in psoriasis. (January 2014) - Christophers, E.; Metzler, G.; Röcken, M.
Summary Psoriasis is an immune‐regulated skin disease with various clinical subtypes and disease activities. The majority of patients present with predominantly stable plaques. At the onset of new lesions, plaque‐type psoriasis frequently demonstrates pin‐sized and highly inflammatory papules sometimes with an inflammatory border. The histopathology of initial psoriasis differs from stable plaque‐type psoriasis. Early lesions demonstrate innate immune cells with neutrophils, degranulating mast cells and macrophages. These are followed by interleukin (IL)‐1‐dependent T helper (Th)17 cells, finally resulting in the Th1‐dominated immunopathology of stable plaque‐type psoriasis, where mononuclear cells predominate with interspersed neutrophilic (Munro) microabscesses. These features suggest a bimodal immune pathway where alternate activation of either innate (autoinflammatory) or adaptive (autoimmune) immunity predominates. Neutrophilic infiltrations appear during early psoriasis with Munro abscesses. They are time limited and occur periodically, clinically best seen in linear nail pitting. These features strongly suggest a critical role for an IL‐1–Th17‐dominated autoinflammation in the initiation of psoriasis, followed by a Th1‐dominated late‐phase reaction. The concept of bimodal immune activation helps to explain results from therapeutic interventions that are variable and previously only partly understood.